Evaluation of medical supplies essential for the care of survivors of sex- and gender-based violence in post-conflict Eastern Democratic Republic of Congo - Rybarczyk, Megan; Tosha, Mafille; Mbika, Bicky; Bulonza, Patricia; Ramazani, Paul; Zahiga, Isaya; Safari, Octave; Bachunguye, Richard; Safari, Christian; Iragi, Aline; Glass, Nancy (Medicine, conflict, and survival, 2011)
The fundamental concepts set forth in the formal Post-Conflict Needs Assessment (PCNA) initiative created by the United Nations Development Group have the potential to be adapted to assist local groups in documenting the needs of and the provision of health care to survivors of sex- and gender-based violence (SGBV) in Eastern Democratic Republic of Congo (DRC). In partnership with Congolese health care providers, we took the first step in advocating for a locally-adapted and focused needs assessment through the development and administration of surveys to providers in the South Kivu Province, DRC. The content of the surveys was largely based on lists of medical supplies deemed essential for reproductive health and for the care of survivors by the Reproductive Health Response in Crises Consortium. The providers in both urban and rural settings considered many of the supplies identified on the surveys necessary for the care of survivors (84%; p < 0.05) but considered few accessible (26%; p < 0.05) in their particular clinical settings. Providers also felt that the existing list of supplies was inadequate to meet the needs of survivors, and also that providers needed ongoing training to improve supply procurement and management, more knowledge of the needs of male survivors of SGBV, and more educational opportunities to improve the quality of care to survivors. Given the deficiencies expressed by providers in the surveys, this study demonstrated a critical need for a locally-adapted and focused needs assessment to improve health services to survivors.